Optimalisasi Pemahaman Materi Cerpen Melalui Media Wordwall Pada Siswa Kelas XI SMA Islam Az Zahrah Palembang - Sefti Ninis Ariska; Emawati Emawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Effective learning requires creative and interactive approaches to enhance students' understanding of the material. This study focuses on evaluating the use of Wordwall as a learning tool for short stories in grade 11 at SMA Islam Az-Zahrah Palembang. The main focus of learning includes the definition, characteristics, and types of short stories. Through the